R2N Sustainable environmental education in EFL elementary textbook: a content analysis - Emylia Malik; Istiqomah Nur Rahmawati (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2026)
This study investigates how sustainability messages are represented in an English as a Foreign Language (EFL) textbook for Indonesian elementary learners and the extent to which these messages reflect SDG/ESD priorities. Using qualitative content analysis of multimodal content with particular attention to visual illustrations, the study examines the Grade IV textbook My Next Words to identify recurring environmental themes and the sustainability practices promoted. The findings show that sustainability is primarily framed through everyday, learner-accessible routines, including reducing single-use plastic during shopping; maintaining cleanliness at home and school; choosing low-impact mobility (e.g., cycling); saving energy by turning off lights; and caring for plants through watering and tree planting, which collectively model ecological responsibility for young learners. However, the coverage remains uneven: more systemic sustainability dimensions, especially renewable energy literacy, structured waste management (sorting and recycling routines), and explicit, solution-oriented climate change learning, are limited, resulting in sustainability being communicated more as individual moral behavior than as interconnected environmental challenges requiring informed understanding and collective action. The study recommends strengthening future textbook editions by integrating more balanced sustainability dimensions through age-appropriate tasks, projects, and visuals linked to local contexts, alongside teacher support to help learners move from “doing” sustainability to understanding its broader environmental rationale, thereby enhancing environmental literacy and SDG/ESD-aligned learning in primary EFL education in Indonesia.